Barriers to healthy lifestyle behaviours and adherence to physical activity and dietary guidelines by older Australians: A descriptive analysis - Gadowski, Adelle M.; Curtis, Andrea J.; Heritier, Stephane; Zoungas, Sophia; Owen, Alice J. (Human nutrition & metabolism, 2021)
To examine adherence to physical activity (PA) and dietary guidelines, explore barriers to healthy lifestyle behaviours, and determine any associations with lipid-lowering drug therapy (LLT). Cross-sectional analysis of self-reported PA using the International Physical Activity Questionnaire for Elderly (IPAQ-E), diet using the Australian Short Dietary Screener (Aus-SDS), and perceived barriers to healthy PA and dietary behaviours. Australia A convenience sample of 110 community-dwelling Australian adults aged ≥70 years. Descriptive statistics and Pearson's χ2 were used to analyse adherence to guidelines and lifestyle barriers. Of 110 adults (mean age 76.8 ± 4.5y), 51.8% met PA guidelines, and none met all five dietary guidelines. Lipid-lowering drug therapy users engaged in less weekly PA (median 155, IQR = 70, 370 min) than non-users (median 420, IQR = 210, 675 min). Dietary intake did not differ by LLT status. Mobility and health concerns (68.1% vs 23.7%), and motivation (79.2% vs 36.8%) were more common barriers to PA among LLT users compared with non-users (p < 0.001). Perceived dietary barriers did not differ by LLT use. Half the study population met PA guidelines; however, none met all dietary guidelines. In older adults, targeted interventions addressing common barriers to achieving healthy lifestyles and reducing the risk of chronic disease are needed, especially among LLT users. •Approximately half of participants met physical activity guidelines.•No participants met dietary guidelines for all food groups.•Lipid-lowering therapy users exercised less than non-users.•Mobility and health concerns were more common among lipid-lowering therapy users.•Barriers to dietary intake and behaviours did not differ by lipid-lowering therapy use.